2006
DOI: 10.1055/s-2006-925229
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Transesophageal Drainage of a Mediastinal Pancreatic Pseudocyst

Abstract: We read with great interest the recent ar− ticle by Jonas et al. [1] which described the endoscopic ultrasound− (EUS−)guided drainage of a cystic metastasis in the mediastinum, and also the article by Mohl et al. [2] reporting their experience of endoscopic transhiatal drainage of a mediastinal pancreatic pseudocyst. Both articles reported interesting cases of EUS− guided or EUS−assisted drainage of med− iastinal lesions. We recently managed a similar case, a patient with a large pancre− atic pseudocyst that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…3,6,12 EUS and EUS-guided FNA is an important diagnostic tool for the evaluation of mediastinal pseudocysts, and it can help in determining the extent of solid necrotic debris and thus help in planning the optimal therapy. 8 The ideal management of mediastinal pseudocysts is not entirely clear and depends on the underlying etiology, ductal anatomy, size of the pseudocyst, and availability of expertise. Small pseudocysts may resolve spontaneously, but this is a rare event and requires prolonged conservative management including somatostatin or its analogues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6,12 EUS and EUS-guided FNA is an important diagnostic tool for the evaluation of mediastinal pseudocysts, and it can help in determining the extent of solid necrotic debris and thus help in planning the optimal therapy. 8 The ideal management of mediastinal pseudocysts is not entirely clear and depends on the underlying etiology, ductal anatomy, size of the pseudocyst, and availability of expertise. Small pseudocysts may resolve spontaneously, but this is a rare event and requires prolonged conservative management including somatostatin or its analogues.…”
Section: Discussionmentioning
confidence: 99%
“…6 Literature supporting the endoscopic drainage of mediastinal pseudocysts is scant. 3,5,[7][8][9] We previously reported cases of successful resolution of pancreatic pseudocysts at mediastinal as well as various other atypical locations by endoscopic transpapillary drainage, and these cases are also included here. [2][3][4][5]9 In this case study, we describe the clinical and radiological characteristics of mediastinal pseudocysts in 12 patients (the cases of 4 of these patients were published previously as case reports or their data included in a previously published article) 3,5,9 as well as our experience with endoscopic drainage and clinical outcome in these patients.…”
mentioning
confidence: 99%
“…While endoscopic drainage has been successfully used in patients with abdominal pseudocysts, there are only a few reports describing successful resolution of mediastinal pseudocysts with endoscopic interventions [3,6,8,19,[30][31][32][33][34][35]. Mallavarapu et al [31] reported two patients with mediastinal pseudocyst.…”
Section: Discussionmentioning
confidence: 99%
“…Topa et al [6] and Komtong et al [34] also reported successful resolution of mediastinal pseudocyst by endoscopic transgastric drainage. Gupta et al [8] and Saftoiu et al [35] have described successful resolution of mediastinal pseudocyst by EUS-guided transesophageal drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is safe even in the presence of extensive collateral circulation, since the transgastric puncture of the pancreatic duct does not require coagulation or cutting. Although EUS-assisted or EUS-guided drainage procedures can be done safely, these should be limited for the moment to tertiary centers with trained endoscopists, large caseloads, backed by expertise in interventional radiology and skilled pancreatic surgery support [18] . The utility of these mini-invasive combined endoscopic procedures for the management of difficult cases of chronic pancreatitis should be established by further prospective studies.…”
Section: Discussionmentioning
confidence: 99%